Racial disparities in family-provider interactions for pediatric asthma care. (3rd April 2018) - Trivedi, Michelle; Fung, Vicki; Kharbanda, Elyse O.; Larkin, Emma K.; Butler, Melissa G.; Horan, Kelly; Lieu, Tracy A.; Wu, Ann Chen
ABSTRACT: Objective : Black and Latino children experience significantly worse asthma morbidity than their white peers for multifactorial reasons. This study investigated differences in family-provider interactions for pediatric asthma, based on race/ethnicity. Methods : This was a cross-sectional study of parent surveys of asthmatic children within the Population-Based Effectiveness in Asthma and Lung Diseases Network. Our study population comprised 647 parents with survey response data. Data on self-reported race/ethnicity of the child were collected from parents of the children with asthma. Outcomes studied were responses to the questions about family-provider interactions in the previous 12 months: (1) number of visits with asthma provider; (2) number of times provider reviewed asthma medications with patient/family; (3) review of a written asthma treatment plan with provider; and (4) preferences about making asthma decisions. Results : In multivariate adjusted analyses controlling for asthma control and other co-morbidities, black children had fewer visits in the previous 12 months for asthma than white children: OR 0.63 (95% CI 0.40, 0.99). Additionally, black children were less likely to have a written asthma treatment plan given/reviewed by a provider than their white peers, OR 0.44 (95% CI 0.26, 0.75). There were no significant differences by race in preferences about asthma decision-making nor in the frequency of asthma medication review. Conclusion : Black children with asthma have fewer visits with their providers and are less likely to have a written asthma treatment plan than white children. Asthma providers could focus on improving these specific family-provider interactions in minority children.